Developing an integrated CO2 capture and mineralization process with lower energy consumption - K. H. Tham; T. Seah; Q. Y. Kouk; W. Goh; S. Cheng; C. Wang; J. Bu; L. Tao (International Journal of Energy and Water Resources, 2025)

Mesenchymal stem cell therapy in hypertrophic and keloid scars - Christine Bojanic; Kendrick To; Adam Hatoum; Jessie Shea; K. T. Matthew Seah; Wasim Khan; Charles M. Malata (Cell and Tissue Research, 2021)
Scars are the normal outcome of wound repair and involve a co-ordinated inflammatory and fibrotic process. When a scar does not resolve, uncontrolled chronic inflammation can persist and elicits excessive scarring that leads to a range of abnormal phenotypes such as hypertrophic and keloid scars. These pathologies result in significant impairment of quality of life over a long period of time. Existing treatment options are generally unsatisfactory, and there is mounting interest in innovative cell-based therapies. Despite the interest in mesenchymal stem cells (MSCs), there is yet to be a human clinical trial that investigates the potential of MSCs in treating abnormal scarring. A synthesis of existing evidence of animal studies may therefore provide insight into the barriers to human application. The aim of this PRISMA systematic review was to evaluate the effectiveness of MSC transplantation in the treatment of hypertrophic and keloid scars in in vivo models. A total of 11 case-control studies were identified that treated a total of 156 subjects with MSCs or MSC-conditioned media. Ten studies assessed hypertrophic scars, and one looked at keloid scars. All studies evaluated scars in terms of macroscopic and histological appearances and most incorporated immunohistochemistry. The included studies all found improvements in the above outcomes with MSC or MSC-conditioned media without complications. The studies reviewed support a role for MSC therapy in treating scars that needs further exploration. The transferability of these findings to humans is limited by factors such as the reliability and validity of the disease model, the need to identify the optimal MSC cell source, and the outcome measures employed.

Quantifying the Roles of Tidal Volume and PEEP in the Pathogenesis of Ventilator-Induced Lung Injury - Adrian S. Seah; Kara A. Grant; Minara Aliyeva; Gilman B. Allen; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Use of NS 3 consensus primers for the polymerase chain reaction amplification and sequencing of dengue viruses and other flaviviruses - V. T. K. Chow; Catherine L. K. Seah; Y. C. Chan (Archives of Virology, 1993)